Corticosteroids for Bacterial Keratitis: The Steroids for Corneal Ulcers Trial (SCUT) - Srinivasan, Muthiah (2011)
OBJECTIVE: To determine whether there is a benefit in clinical outcomes with the use of topical corticosteroids as adjunctive therapy in the treatment of bacterial corneal ulcers. METHODS: Randomized, placebo-controlled, double-masked, multicenter clinical trial comparing prednisolone sodium phosphate, 1.0%, to placebo as adjunctive therapy for the treatment of bacterial corneal ulcers. Eligible patients had a culture-positive bacterial corneal ulcer and received topical moxifloxacin for at least 48 hours before randomization. MAIN OUTCOME MEASURES: The primary outcome was best spectacle-corrected visual acuity (BSCVA) at 3 months from enrollment. Secondary outcomes included infiltrate/scar size, reepithelialization, and corneal perforation. RESULTS: Between September 1, 2006, and February 22, 2010, 1769 patients were screened for the trial and 500 patients were enrolled. No significant difference was observed in the 3-month BSCVA (−0.009 logarithm of the minimum angle of resolution [logMAR]; 95% CI, −0.085 to 0.068; P = .82), infiltrate/scar size (P = .40), time to reepithelialization (P = .44), or corneal perforation (P > .99). A significant effect of corticosteroids was observed in subgroups of baseline BSCVA (P = .03) and ulcer location (P = .04). At 3 months, patients with vision of counting fingers or worse at baseline had 0.17 logMAR better visual acuity with corticosteroids (95% CI, −0.31 to −0.02; P = .03) compared with placebo, and patients with ulcers that were completely central at baseline had 0.20 logMAR better visual acuity with corticosteroids (−0.37 to −0.04; P = .02). CONCLUSIONS: We found no overall difference in 3-month BSCVA and no safety concerns with adjunctive corticosteroid therapy for bacterial corneal ulcers. APPLICATION TO CLINICAL PRACTICE: Adjunctive topical corticosteroid use does not improve 3-month vision in patients with bacterial corneal ulcers.